2021
DOI: 10.1123/ijsnem.2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Collagen Peptides on Recovery Following Eccentric Exercise in Resistance-Trained Males—A Pilot Study

Abstract: The authors sought to determine whether consuming collagen peptides (CP) enhances musculoskeletal recovery of connective tissues following a damaging exercise bout. Resistance-trained males consumed 15 g/day of CP (n = 7) or placebo (n = 8), and after 7 days, maximal voluntary isometric contraction (MVIC), countermovement jump height, soreness, and collagen turnover were examined. Five sets of 20 drop jumps were performed and outcome measures were collected 24, 48, and 120 hr postexercise. Countermovement jump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…One article [ 12 ] showed that 150 drop-jumps caused muscle soreness and reduced countermovement-jump height, and that consumption of CPs for 1 week appeared to decrease muscle soreness after 48 hours and accelerated recovery of jump height after 48 hours. The other [ 13 ] reported a pilot study showing that consuming CPs for 1 week alleviated the countermovement jump-height reduction after 100 drop-jumps but not muscle soreness. Therefore, these and our trials showed certain benefits for post-exercise physical condition and fitness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One article [ 12 ] showed that 150 drop-jumps caused muscle soreness and reduced countermovement-jump height, and that consumption of CPs for 1 week appeared to decrease muscle soreness after 48 hours and accelerated recovery of jump height after 48 hours. The other [ 13 ] reported a pilot study showing that consuming CPs for 1 week alleviated the countermovement jump-height reduction after 100 drop-jumps but not muscle soreness. Therefore, these and our trials showed certain benefits for post-exercise physical condition and fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the effects of CPs on post-exercise physical condition and fitness, Clifford et al [ 12 ] showed that 150 drop-jumps caused muscle soreness and reduced countermovement-jump height, but after taking CPs in advance of exercise, muscle soreness probably decreased, and the recovery of jump-height accelerated. In a pilot study, Prowting et al [ 13 ] reported that CPs intake in advance alleviated jump-height reduction after 100 drop jumps although it did not reduce the muscle soreness. These results indicate that regular intake of CPs could positively affect muscle soreness and muscle strength after intense exercise for young males regularly engaged in recreational activities or resistance training.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have also noted the possible positive effects of these collagen derived peptides. Exercise combined with 15-20 g of collagen hydrolysates, preferably after training, for over a week, leads to an improvement in lean body mass, and reduces joint and muscle pain in athletes and physically active people (101)(102)(103)(104)(105)(106). The mechanisms by which the collagen peptides exerted their effect have not yet been elucidated.…”
Section: Protein Hydrolysates In Joint Sorenessmentioning
confidence: 99%
“…Alternatively, with respect to dosage, Bongers et al did not detect significant differences between treatment and control groups in knee pain, function, inflammation, or biomarkers of bone synthesis with 10 g/day collagen peptide supplementation over 12 weeks in older adults with self-reported knee pain [24]. As improved function and pain have only been observed with acute collagen peptide supplementation in the presence of a specific injury, their lack of significant findings may be because of the short study duration, especially in the absence of a specific injury [24,25]. Also, prior studies report improvements in pain and function when combined with rehabilitative or resistance training programs [26,27].…”
Section: Pain and Functionmentioning
confidence: 99%